Income Guarantees and Borrowing in Risky Environments: Evidence from India's Rural Employment Guarantee Scheme. (20th November 2019) - Bell, Clive; Mukhopadhyay, Abhiroop
Abstract : This paper investigates the effects of an income guarantee on borrowing in a risky setting with marked seasonality. A three‐season, infinite‐horizon model is developed, in which the aims of smoothing consumption and maintaining creditworthiness are somewhat opposed and the seasonal timing of transfers matters. If borrowing does not affect production, then larger transfers concentrated in the lean season may well lead to a contraction of the total amount borrowed over the whole annual cycle. If borrowing also finances working capital, then larger transfers make riskier positions attractive, and investment in working capital and total borrowing may both increase. These insights are tested in the context of India's National Rural Employment Guarantee Scheme, as implemented in upland Odisha. The potential endogeneity of participation is addressed by using the female reservation for local elections as an instrument. Each day's work reduces the estimated level of borrowing in the lean season by about the regulated wage. In contrast, the estimated effect on borrowing in the cultivation season by households owning at least the median holding is to increase it by about one‐and‐a‐half times the wage; but there is no significant effect for households owning less.